Dukungan Keluarga bagi Kemandirian Lansia - Jajuk Kusumawaty; Dedi Supriadi; Ima Sukmawati; Adi Nurapandi (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between family support and the independence of older people in Cigembor Village, Ciamis Regency. The method used is quantitative research with a cross-sectional approach. The results showed that the highest family support was in the supportive category, namely 66 people (68.0%). At the same time, the highest level of independence for older people is in the total independent category, namely 55 people (56.7%). In conclusion, there is a relationship between family support and elderly independence. Keywords: Family support, Independence, Elderly